A high-precision time-domain RRAM state control approach. (April 2018) - Bagheri-Soulla, A.A.; Ghaznavi-Ghoushchi, M.B.
Abstract: RRAM as an analog-like element could be utilized in many interesting applications. Highly non-linear characteristics and fabrication related variations are the most important obstacles in its analog applications. To use the device in analog domain, it is required to increase the state adjustability and consider variations effects. In this paper we propose an approach, which leads to precise control of RRAM's gap length in time domain. To have a feedback of device variations a process sensor is introduced and utilized. The main idea and two proposed circuit level implementations are discussed. The applicability of the proposed method and circuits have been shown using circuit level simulations.